Social Capital and Its Transformations in Sidogiri Islamic Boarding School - Kutsiyah, Farahdilla (KARSA: Journal of Social and Islamic Culture, 2020)
Treasures about Islam in Indonesia cannot be separated from pesantren (Islamic boarding school). The contribution to the development of social and cultural, especially through the preservation of local culture. This paper discusses social capital and its transformations in Pondok Pesantren Sidogiri, Pasuruan Regency. This study applied ethnography method. The research findings show  internalized social capital includes social interaction ties  such as  routine recitations, alumni bonds, and togetherness inthe style of pondok pesantren, istighozah, haul,  akhir sanah and cooperation with other institutions outside pesantren. Norms consist of love and obedience to masyaikh also his family, santri Sidogiri are one brotherhood, discipline, barokah (divine blessing), and independence in the economy, as well as honest and trustworthy behavior. Shared vision contain the development of science and institutions for the affirmation of ahlus Sunnah wa jamaah, khidmah lil ma’had khidmah lil ummah, ibadillah sholihin, simplicity, and creating entrepreneurship. Meanwhile, the transformation of social capital are the expansion of the pesantren network through the development of the organizational structure - establishment of new institutions and institutionalize of khidmah lil ma'had and khidmah lil ummah. The social capital has a big enough impact, not only to create santri who own a strong religious knowledge and entrepreneurial spirit but also as a major trigger in the success of Pondok Pesantren Sidogiri in developing its economic business. The productive culture attached to social capital, moreover the increasing stock of social capital intend to combines two aspects namely clinging ahlusunnah wal jamaah and responding to advancement of science and technology.